Who are the patients that "do not need" any follow-up care after percutaneous coronary intervention?. (2nd July 2022) - Hjertvikrem, N; Brors, G; Instenes, I; Falun, N; Pettersen, T R; Rotevatn, S; Norekval, T M
Abstract: Funding Acknowledgements: Type of funding sources: Public Institution(s). Main funding source(s): Western Norway Health Authority 2017-2020 (no 912184) Norsk Sykepleierforbund - (Norwegian Nurses Association) Background: Personalised follow-up care based on patients' preferences may increase adherence to secondary prevention strategies. Still, some patients do not see the need for follow-up care and information after percutaneous coronary intervention (PCI). Furthermore, associations between perceived need for follow-up care, received follow-up care, health state and socio-demographic characteristics are scarcely investigated. Purpose: To determine the association between the patients' perceived need of follow-up care and information, health states and socio-demographic characteristics after PCI. Methods: CONCARDPCI is a prospective multicentre cohort study including 1970 patients after PCI. The study was conducted at three Norwegian referral PCI centres. Clinical data were collected from patients' medical records and the Norwegian Registry on Invasive Cardiology. Socio-demographic characteristics were obtained by self-report during index hospitalization after PCI. Mental and physical health were measured using the disease-specific Myocardial Infarction Dimensional Assessment Scale and the generic RAND-12 questionnaire. Perceived need for follow-up and information, and use of care were obtained at two and 12-months. Logistic regression was performed to scrutinize the aims. Results: Patients were predominantly men (78%) with a mean age of 66 years (SD 11, men 65, women 69, p<0.001). Significantly more men than women reported "do not need follow-up" (16% vs. 12%, p=0.050) and "do not need information" (8% vs. 5%, p=0.031) after two months. From two to 12 months the proportion of women that reported "do not need follow-up" doubled (p<0.001). Three times as many women reported "do not need information" from two months (5%) to 12 months (15%) ( p<0.001). At 12 months, there was no longer a significant difference between men and women. For women, living alone (p=0.007) and having three or more comorbidities (compared to no comorbidities) (p=0.011) were significantly associated with "do not need follow-up" and "do not need information." Men with higher education (p=0.006) were less likely to report "do not need follow-up" and "do not need information" than men with primary school. Age (p<0.001), two or more comorbidities (p=0.019), and good disease-specific physical health (p=0.017) were significantly associated with increased likelihood to report "do not need follow-up" and "need no information" for men. Higher scores on disease-specific insecurity made (p= 0.010) men less likely to answer "do not need follow up" and "need no information". Not receiving any follow-up care increased with age (p=0.032). Patients reporting poor disease-specific physical health were less likely to "have not received follow-up" (p=0.002). Conclusions: Patients' perceived need for follow-up care and information is decreasing over time. This implies that patients' follow-up care must be provided shortly after PCI in order to increase adherence to secondary prevention strategies.